Amphibia, Anura, Eleutherodactylidae, Diasporus anthrax (Lynch, 2001) : New records and geographic distribution (2012)
ABSTRACT: During fieldwork in the Departamentos of Antioquia and Santander we found several specimens of Diasporus anthrax. The new records extend northward its known geographic distribution. We report, for the first time, the presence of D. anthrax on the Cordillera Oriental and discuss some taxonomic implications of these new findings.